Pedestrian Bridge over the S. Pedro Estuary, Aveiro. Portugal - Sequeira, Marta (TC Cuadernos, 2022)
The Pedestrian Bridge over the São Pedro estuary joins two parts of the Campus of the University of Aveiro: the Santiago Bridge, whose origin dates back to the 1970s, and the Crasto Bridge, which dates back to the 1990s. It crosses a complex lagoon system, in an area which is established as a great flood plain and where the morphological and edaphoclimatic conditions have allowed the formation of an ecosystem with unique properties in the country. The original intention of the university rectory was, for ecological reasons, to create a wooden bridge that would walk close to the water surface, to which an alternative was proposed: to design a high bridge with few supports – in order to minimise the interaction with the ecological system of the Esteiro de São Pedro – using a metallic structure – so as to guarantee its longevity. This hypothesis, simple and effective, allowed to generate a somewhat anachronistic image, dialoguing explicitly with the memory of the metallic bridges of the 19th century that we all carry.